Teaching White Papers Through Client Projects - Willerton, Russell (Business Communication Quarterly, 2013)
White papers are increasingly prevalent in business and professional settings. Although textbook resources for white paper assignments are limited, a white paper assignment completed for a community client can provide a learning experience that students enjoy and that strengthens ties between the university and the community. This article describes a way to approach the white paper assignment in a communications-focused course and identifies resources to support white paper assignments.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDgwNTY5OTEyNDU0NzEz